Die in pieces: How Drosophila sheds light on neurite degeneration and clearance. (20th April 2019) - Sapar, Maria L.; Han, Chun
Abstract: Dendrites and axons are delicate neuronal membrane extensions that undergo degeneration after physical injuries. In neurodegenerative diseases, they often degenerate prior to neuronal death. Understanding the mechanisms of neurite degeneration has been an intense focus of neurobiology research in the last two decades. As a result, many discoveries have been made in the molecular pathways that lead to neurite degeneration and the cell-cell interactions responsible for the subsequent clearance of neuronal debris. Drosophila melanogaster has served as a prime in vivo model system for identifying and characterizing the key molecular players in neurite degeneration, thanks to its genetic tractability and easy access to its nervous system. The knowledge learned in the fly provided targets and fuel for studies in other model systems that have further enhanced our understanding of neurodegeneration. In this review, we will introduce the experimental systems developed in Drosophila to investigate injury-induced neurite degeneration, and then discuss the biological pathways that drive degeneration. We will also cover what is known about the mechanisms of how phagocytes recognize and clear degenerating neurites, and how recent findings in this area enhance our understanding of neurodegenerative disease pathology.